Exposure of Ophthalmologists to Patients' Exhaled Droplets in Clinical Practice: A Numerical Simulation of SARS-CoV-2 Exposure Risk - Fan, Yanchao; Liu, Li; Zhang, Hui; Deng, Yingping; Wang, Yi; Duan, Mengjie; Wang, Huan; Wang, Lixiang; Han, Leifeng; Liu, Yalin (Frontiers in Public Health, 2021)
Background: Lack of quantification of direct and indirect exposure of ophthalmologists during ophthalmic diagnostic process makes it hard to estimate the infectious risk of aerosol pathogen faced by ophthalmologists at working environment. Methods: Accurate numerical models of thermal manikins and computational fluid dynamics simulations were used to investigate direct (droplet inhalation and mucosal deposition) and indirect exposure (droplets on working equipment) within a half-minute procedure. Three ophthalmic examination or treatment scenarios (direct ophthalmoscopic examination, slit-lamp microscopic examination and ophthalmic operation) were selected as typical exposure distance, two breathing modes (normal breathing and coughing), three levels of ambient RH (40%, 70% and 95%) and three initial droplet sizes (50 μm, 70 μm and 100 μm) were considered as common working environmental condition. Results: The exposure of an ophthalmologist to a patient’s expiratory droplets during a direct ophthalmoscopic examination was found to be 95 times that of a person during normal interpersonal interaction at a distance of 1 m and 12.1 times, 8.8 times and 9.7 times that of an ophthalmologist during a slit-lamp microscopic examination, a surgeon during an ophthalmic operation and an assistant during an ophthalmic operation, respectively. The ophthalmologist’s direct exposure to droplets when the patient cough-exhaled was approximately 7.6 times that when the patient breath-exhaled. Compared with high indoor RH, direct droplet exposure was higher and indirect droplet exposure was lower when the indoor RH was 40%. Conclusion: During the course of performing ophthalmic examinations or treatment, ophthalmologists typically face a high risk of SARS-CoV-2 infection by droplet transmission.